Cassava–soybean intercropping alleviates continuous cassava cropping obstacles by improving its rhizosphere microecology - Chen, Huixian; Ruan, Lixia; Cao, Sheng; He, Wen; Yang, Haixia; Liang, Zhenhua; Li, Hengrui; Wei, Wanling; Huang, Zhenling; Lan, Xiu (Frontiers in Microbiology, 2025)
IntroductionContinuous cropping is the main cause of cassava yield reduction. To find an effective method to alleviate the obstacle of cassava continuous cropping and explore the effect of cassava–soybean intercropping, this study analysed the differences in cassava agronomic traits, yield, soil physicochemical properties, microbial community structure, and metabolites between cassava single cropping (M) and cassava–soybean intercropping (MD) and its effects on continuous cassava cropping soil.MethodsThe correlations between yield, agronomic traits, soil physicochemical properties, microbial diversity, and metabolites were explored, and the effect of the cassava–soybean intercropping model on cassava soil was revealed.ResultsThe results showed that compared with group M, soil pH, porosity, organic matter, available nitrogen, and fresh potato yield in the MD group significantly increased by 8.59, 13.66, 20.68, 23.29, and 50.61%, respectively, and soil bulk density significantly decreased by 9.68%. Soil bacterial community diversity in the MD group did not change significantly but had significant effects on soil fungal community diversity. The relative abundances of Trichoderma and Micropsalliota in the MD group were significantly upregulated. The contents of phenol glucuronide, 2,3-butanediol, L-phenylalanine, deoxyguanosine, other carbohydrates, alcohols, purine nucleotides, and amino acids in the soil of the MD group were significantly upregulated. Organic acids, such as fumaric acid, succinic acid, phosphoenolpyruvic acid, decreased significantly. Correlation analysis showed that Trichoderma was significantly negatively correlated with fumaric acid, succinic acid, phosphoenolpyruvic acid, and soil bulk density. However, there was significant positive correlation with phenol glucuronide, alpha-CEHC deoxyguanosine and other carbohydrates, nucleotide substances, organic matter, and pH. Phenol glucuronide, 2,3-butanediol, L-phenylalanine, deoxyguanosine and other carbohydrates, alcohols, purine nucleotides, and amino acids were significantly positively correlated with organic matter, available nitrogen, soil porosity, and pH.DiscussionTherefore, cassava–soybean intercropping can effectively alleviate the obstacles of continuous cassava cropping by affecting the accumulation of metabolites and microbial community structure in continuous cropping soil, thereby improving the adverse factors of severe soil acidification, soil compaction, and nutrient decline.